Perhitungan Struktur Laboratorium Teknik Sipil Type II Fakultas Teknik Universitas Muhammadiyah (UMSU) Medan - Gunawan, Randi; Dewi, Irma; Gultom , Muhammad Husin; Ajinar (Journal of Engineering and Science, 2022)
The lack of supporting infrastructure facilities such as the Laboratory at Samudra University, especially in the Civil Engineering Study Program, Faculty of Engineering, has resulted in Iskandar Thani Institute having to work hard in building infrastructure to keep pace with advances in technology and science. This study aims to plan the dimensions and reinforcement of beams, columns, plates and stairs in the Civil Engineering Laboratory building. The laboratory building to be analyzed has a total of 3 floors with floor dimensions of 43 m x 27.49 m. Modeling and analysis of the structure of this building is assisted by the SAP2000 program using the Special Moment Bearing Frame System (SPRMK) and is designed according to SNI 03-1726-2012, SNI 03-2847-2013, and PPPURG 1987. The structure is planned to use concrete quality fc' 30 MPa and steel grade fy 400 MPa. The results of the analysis obtained that the floor slab thickness was 13 cm using D10-200 mm reinforcement for main reinforcement and D10-300 mm for split reinforcement. The thickness of the roof slab is 12 cm using D10-200 mm reinforcement for main reinforcement and D10-300 mm for split reinforcement. The dimensions of the B1 beam are 50 cm x 70 cm using 12D25 for the support area with D10-80 mm braces and 8D25 reinforcement for the field area with D10-120 mm braces. Begel B2 30 cm x 50 cm using 4D25 reinforcement for the support area and field with braces for D10-200 mm field and braces for D10-100 mm support. The dimensions of the K1 column are 60 cm x 80 cm using 10D25 reinforcement with D10-300 mm begel. The dimensions of the K2 column are 60 cm x 60 cm using 8D25 reinforcement with D10 -200 mm begel. The thickness of the ladder plate and landing was obtained 13 cm using D10-200 mm reinforcement.